Onyx and Marmer Objects Modeling by Joining and Choosing Parametric 2) 1) Modifications of Bezier Revolution Surfaces - Kusno Kusno; Antonius Cahya P; Mahros Darsin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2007)
We formulate application of Bezier revolution surfaces for modeling onyx and marmer objects in three steps as the following. Firstly, calculating the parametric representation of Bezier revolution surfaces and its shape modification in some different forms is done. Secondly, we formulate parametric continuity for joining the surfaces. Finally, the application of those formulas for modeling onyx and marmer objects of revolution by using computer are simulated.